Desain Rekayasa dan Analisis FEA Mesin Depackaging Sampah Tipe Hammer Mill - Fakhri Iqbal Maulana; Sigit Mujiarto; Arif Rahman Saleh (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Management of household waste in Final Disposal Sites (TPA) faces a serious problem, where most of the waste accumulates and is difficult to decompose due to its complex nature. This condition substantially inhibits natural decomposition processes and limits the effectiveness of recycling efforts. Pre-processing operations, such as sorting and crushing, which are still dominated by manual methods, are proven to be inefficient, high-risk, and require large allocations of land resources and manpower. Therefore, automated technological innovation is needed to facilitate the efficient separation of organic components from inorganic materials (packaging). This research was conducted to determine the design and structural strength analysis of a hammer mill type depackaging machine, carried out using Solidworks software. Structural analysis simulation utilizes Finite Element Analysis (FEA) to determine the structural strength of the machine. The specifications of the hammer mill type depackaging machine include a capacity of 3000 kg/hour, a hammer mill input power of 12 KW, and a rotational speed of 2500 rpm with a torque of 34.54 Nm. Meanwhile, the screw conveyor input power is 0.75 KW and the rotational speed is 20 rpm. The FEA simulation analysis results for the hammer mill type depackaging machine showed that the maximum Von Mises stress value recorded is 3,022×10^7 N⁄m^2 , the maximum displacement value measured is very minimal, namely 2,793×10^(-1) mm, and the Factor of Safety (FOS) obtained is 8.3. This FOS value significantly exceeds the required minimum safety limit (>3), confirming that the machine design has optimal reliability, fatigue resistance, and structural integrity for operation under intensive working conditions at the TPA. The conclusion of this study indicates that the engineering design of this hammer mill type depackaging machine is safe and meets structural technical requirements to proceed to the implementation phase, potentially becoming a sustainable technological solution in improving the efficiency of waste pre-processing.